The Pandemic and Teachers: How Teachers’ Daily Life in the Classroom Has Been Impacted - Bailey Mahoney (Educational Considerations, 2023)
This study explores how the COVID-19 pandemic has affected educators during the end of the 2019-2020 school year and throughout the 2020-2021 school year. During a time with so much uncertainty, the focus has been on how best to approach the school year for students. Little conversation has happened concerning the impact on teachers. While research on this topic is limited to the short time span of the pandemic so far, teachers have shifted their instructional strategies, assessment strategies, and homework policies to match the needs of students. The following study seeks to highlight these changes and provide a voice and sounding board for teachers in case another COVID-19-like pandemic occurs.
Keywords: COVID-19; pandemic; instructional strategies; homework; assessment; health and safety; equity; teachers